Interplay Between Endocrine Disruptors and Immunity: Implications for Diseases of Autoreactive Etiology - Popescu, Maria; Feldman, Talia B.; Chitnis, Tanuja (Frontiers in Pharmacology, 2021)
The sex-bias of disease susceptibility has remained a puzzling aspect of several autoimmune conditions, including post-infection viral autoimmunity. In the last half of the twentieth century, the incidence rate of female-biased autoimmunity has steadily increased independent of medical advances. This has suggested a role for environmental factors, such as endocrine disrupting chemicals, which have been described to interfere with endocrine signaling. Endocrine involvement in the proper function of innate and adaptive immunity has also been defined, however, these two areas have rarely been reviewed in correlation. In addition, studies addressing the effects of endocrine disruptors have reported findings resulting from a broad range of exposure doses, schedules and models. This experimental heterogeneity adds confusion and may mislead the translation of findings to human health. Our work will normalize results across experiments and provide a necessary summary relevant to human exposure. Through a novel approach, we describe how different categories of ubiquitously used environmental endocrine disruptors interfere with immune relevant endocrine signaling and contribute to autoimmunity. We hope this review will guide identification of mechanisms and concentration-dependent EDC effects important not only for the sex-bias of autoimmunity, but also for other conditions of immune dysfunction, including post-infection autoreactivity such as may arise following severe acute respiratory syndrome coronavirus 2, Epstein-Barr virus, Herpes Simplex virus (HSV).